Traditional poultry farming in Morocco - Benabdeljelil K.; Arfaoui T.; Johnston P. (2001)
The present article describes rural poultry production systems in Morocco and the role of scavenging chicken in the rural household economy. An extensive survey was conducted aiming to characterize rural poultry farming in order to determine the main constraints to its development and suggest practical improvement means. One hundred and six households in 3 villages were surveyed with a total of 768 inhabitants. Each household owned on average 5.8 hectares (from 0 to 11) and had 5 people. Women represented 49% of the population. Rural poultry farming was essentially a women fs business: 73% of the flocks were managed by women and represented their main activity in 58% of the cases. Fifty four percent of the birds in the flocks were hatched on the farms while 46% were purchased. Poultry represented the predominant species raised on the farms with flock size ranging from 0 to 58. Each household owned on average 11chickens and/or 9 turkeys. The sex ratio was 4.6 and 1.7 females to a male for chickens and turkeys flocks respectively. The local birds, called Beldi were characterized by a wide genetic variability. Rudimentary housing was available for poultry in 79% of the households (an increased ratio compared to 64% in 1986 and 71% in 1993). Local materials such as bamboo, wood, plastic screens and others were used. Rural poultry scavenged mainly around homes and some wheat bran, barley, wheat, maize, compound feed, dry bread and kitchen leftovers were distributed at various times. Rudimentary watering devices were available in 94% of the farms with water supply coming from wells (61%) or natural springs (49%). Sexual maturity was reached at about 154 and 168 days for roosters and hens, and around 217 and 231 days for turkey toms and hens respectively. Sixty-nine days were observed on average between laying cycles. Hens sat on eggs 2 to 3 times a year and hatchability reached 78% for chickens and 80% for turkeys. Egg selection for incubation was based on henperformance, body size, egg size and colour and whether males were available in the flocks. The number of laying hens varied from 0 to 5 per farm. Eggs were laid all year around with a peak in spring (39%) and summer (22% of the households). The number of eggs produced per year was 78 per hen and 69 per turkey hen. High mortality was recorded as a result of diseases and predators (mortality rates reached up to 77%). Local consumption (in 48% of the households) and sales (52%) were the main destinations of local poultry products. A rural household consumed on average 16 chickens and /or 11 turkeys per year. Sales of poultry products took place in ruralmarkets every week. This study revealed that archaic production techniques, rudimentary housing, anarchic crosses and diseases were the major constraints to the development of rural poultry production. Several improvement actions were proposed such as the extension of new production techniques, the distribution of rearing equipment, and others specially targeted for women. The current status and future outlook of rural poultry production are discussed. Future areas of interest for research and development are presented.